Inverter transient response improvement using grey wolf optimizer for type-2 fuzzy control in HVDC transmission link - Ginarsa, I Made; Muljono, Agung Budi; Nrartha, I Made Ari; Seniari, Ni Made; Sultan, Sultan; Zebua, Osea (Institute of Advanced Engineering and Science, 2025)
High voltage direct current (HVDC) on transmission-link becomes a new prominent technology in recent years. The HVDC is applied to transmit amount of electrical energy from power plant to consumers. This method makes reactive power losses on transmission devices decrease significantly and stability level of generator increases. However, inverter HVDC transmission system can produce slow and high inverter transient current (ITC) response at high value of the up-ramp rate. This ITC phenomenon can be serious problem at starting time. So grey wolf algorithm is proposed to optimize input-output parameters of interval type-2 fuzzy control (IT2FC) in inverter-side HVDC. The proposed control performance’s is assessed by integral time squared error (ITSE) and peak overshoot (Mp) approaches. Simulation results show that small ITSE and low Mp of transient response are given by the IT2FC. The IT2FC is successful applied on inverter HVDC with better results compared to conventional PI control scheme.